Clouds Running Out of Juice: A Special Podcast Episode Featuring Tim Winton’s Climate Fiction - Rumen Rachev; Jo Pollitt; Emma Nicoletti (Australian Journal of Environmental Education)
This paper presents a pedagogical experiment in the form of a fictional podcast episode that “aired” in January 2025, featuring Tim Winton’s climate fiction novel Juice (2024). Emerging from a dialogical reading collaboration between three interdisciplinary “scholars, resisters and ordinary grafters” (Winton, 2024, p.116) — Rumen Rachev, Jo Pollitt, and Emma Nicoletti — the paper and podcast operate together through a method we term papercast, centring on three key themes: clouds, atmospheric frictions, and the significance of critically engaging with climate fiction, specifically Juice, amid ongoing climate instability. Simultaneously paper and podcast (papercast), we invite the reader to “listen” visually to the printed material that follows. Through discussion and excerpts from Clouds Running Out of Juice, a creative non-fiction episode of the fictional Ecosophic Generator podcast, the work incorporates AI-generated responses from “listeners” who inhabit the liminal space between present imaginings and future realities. This papercast emerged through asynchronous reading practices and collaborative dialogue, culminating in a three-way conversation that traverses multiple theoretical terrains. Rachev’s investigation as an atmospheric economist into the future-proofing of clouds, Pollitt’s choreographic exploration of everyday weather and experiences of weathering instability, and Nicoletti’s examination of human-atmospheric binaries collectively generate productive tensions between scientific knowledge and creative uncertainty.